Ekonomski vidiki določanja odškodnin v primeru kršitev pravil konkurenčnega prava - Bratina, Tanja (LeXonomica, 2012)
Economic Aspects of the Determination of Damages in Antitrust Cases. Private enforcement of competition law infringements in Slovenia has not been sufficiently developed yet. This is definitely also attributable to the fact that the calculation of the amount of damage suffered because of the infringement of the competition law rules is highly complex and difficult. In order to facilitate the determination of the amount of damages caused by restrictive practices for the parties and the court, the European Commission prepared Draft Guidance Paper on quantifying harm in actions for damages based on breaches of the EU antitrust rules and held a public consultation on that document from 17 June to 30 September 2011. The purpose of this paper is to outline the proposal, both economic and legal aspects, which are contained in the Draft guidelines and to present legislative solutions and case law in that context. Ekonomski vidiki določanja odškodnin v primeru kršitev pravil konkurenčnega prava. Zasebno uveljavljanje kršitev pravil konkurenčnega prava v Sloveniji še ni razvito v zadostni meri. K temu zagotovo prispeva tudi dejstvo, da je samo vprašanje višine škode, ki nastane zaradi kršitve pravil konkurence, izrazito kompleksno in zahtevno. Z namenom olajšanja določanja višine škode, ki je povzročena z omejevalnimi ravnanji, je Evropska komisija strankam in sodiščem junija 2011 dala v javno posvetovanje Osnutek smernic za ocenjevanje škode v odškodninskih tožbah zaradi kršitve člena 101 ali 102 Pogodbe o delovanju Evropske unije. Namen tega prispevka je orisati ekonomske in pravne predloge, ki jih vsebuje Osnutek smernic, ter predstaviti zakonske rešitve in prakso na tem področju.